(untitled) (Veterinary Science, 2022)
Mastitis is a frecuently disease of dairy cattle that leads to a decrease in production and an increase in health costs. This disease can be evaluated through the number of white blood cells per milliliter of milk, which is known as somatic cell count (CCS). Alleles of Bovine Leukocyte Antigen (BoLA) genes were associated with resistance and susceptibility to infectious diseases. The objective of this work was to study the polymorphism of the class II molecules of BoLA-DQA1 and their association with resistance/susceptibility to mastitis measured through the CCS in milk in Holstein cattle from the province of La Pampa. The population was divided into: 1) case group with high CCS and presence of mastitis (≥ 250,000 cel/ml, susceptible) and 2) control group with low CCS (<250,000 cel/ml, resistant). BoLA-DQA1 polymorphisms were genotyped in sixty animals by PCR-RFLP and PCR-SBT. Woolf-Haldane’s Fisher and Odds Ratio (OR) exact test were used to study the association between CCS and allelic variants. 16 alleles of the BoLA-DQA1gene were detected and the BoLA-DQA1*0101 allele showed an OR of 4 (p = 0.58). This finding highlights the importance of BoLA-DQA1 alleles for selection of resistant animals to infectious diseases.